Current Management of Membranous Urethral Strictures Due to Radiation - Waterloos, Marjan; Martins, Francisco; Verla, Wesley; Kluth, Luis Alex; Lumen, Nicolaas (Frontiers in Surgery, 2021)
Radiotherapy is a frequently used treatment for prostate cancer. It does not only causes the intended damage to cancer cells, but also affects healthy surrounding tissue. As a result radiation-induced urethral strictures occur in 2.2% of prostate cancer patients. Management of urethral strictures is challenging due to the presence of poor vascularized tissue for reconstruction and the proximity of the sphincter, which can impair the functional outcome. This review provides a literature overview of risk factors, diagnostics and management of radiation-induced urethral strictures.